The relationship of text to drawings in children’s stories - AlAmeri, Fatima; Alhashemi, Badeeah (Al-Adab Journal, 2025)
The relationship between the text to the drawing is a very old one, its roots extending throughout the ages through the diversity of its characteristics and the styles of its artists, regardless of their tools. Different people and civilizations adopted drawing to express their ideas, lives, achievements, beliefs, and even their journey after death.  Children's story writers invested in this relationship in their writing of children's books from the beginning of the printing era until the modern era.  The interaction between the linguistic text and the visual discourse appeared in their books in a different and a disparate patterns.  Some books follow a method in which the drawings and words tell the same story, by translating the descriptions, colors and shapes provided by the text visually as it is through the executed drawings.  Some of them include interaction in the form in which drawings amplify the meanings of words, giving them an artistic or philosophical dimension, a feeling, an impression, or a reference to an idea.  Contradictory interaction has also appeared in some books, in which there appears to be a contradiction between words and drawings. The drawings do not represent the words nor vice versa. This is an ambiguity that poses a challenge to the recipient in understanding the connection between the words and the drawings and vice versa.  This study seeks to reveal these different forms of the relationship, by providing a historical look at the development of children’s book production from ancient times until the modern era, in addition to explaining the patterns and forms of that interaction by applying it to different models, using the descriptive and analytical approach.